Relationship between septo-valvular angle and risk of pacemaker implantation after transcatheter aortic valve implantation: a preliminary study. Issue 9 (September 2021) - De Stasio, Vincenzo; Cavallo, Armando U.; Spiritigliozzi, Luigi; Pugliese, Luca; Presicce, Matteo; Di Donna, Carlo; Di Tosto, Federica; Pasqualetto, Monia; D'Errico, Francesca; Benelli, Leonardo; Sbordone, Francesco P.; Grimaldi, Francesco; et al.
Abstract : Aim: Pre-transcatheter aortic valve implantation (TAVI) computed tomography (CT) has proven to be crucial in identifying pre- and post-procedural predicting factors predisposing the onset of major arrhythmias that require permanent pacemaker (PPM) implantation caused by the compressive effects of the prostheses on the conduction system at the membranous septum (MS) and the muscular crest of the interventricular septum. Our analysis aims to verify if the pre-TAVI assessment of the angle between the MS and the aortic annulus (SVA) might be a predictive factor for the onset of arrhythmias that requires PPM. Methods: Two cardiovascular specialist radiologists retrospectively and double-blind evaluated a randomized list of preprocedural CT of 57 patients who underwent TAVI with a self-expandable valve from April 2019 to February 2020. Two anatomical features were measured by readers: width of the SVA and MS length (MSL). Results: A PPM was implanted in 18 patients (31%) after the procedure. There was no significant difference in the anatomical measurements performed between the two observers, regarding both anatomical measurements (intraclass correlation coefficient was 0.944 for the SVA and 0.774 for the MSL]. Receiver-operating characteristic curves (ROC) performed for both measurements have documented: for the SVA sensitivity 94% and Negative predictive value (NPV) 96% (area under the curve: 0.77; 95% confidence interval 0.66–0.90). The MSL ROC was not significant. The mean SVA value stratified for patients who did not undergo PPM implantation and patients who did resulted as significant ( P  < 0.005). Conclusion: Measurement of the SVA performed in preprocedural CT scans has proven to be related to the onset of major arrhythmias after TAVI requiring permanent pacemaker implantation with high sensitivity (94%) and NPV (96%).